Exploring the Challenges of Forensic Technology in Responding to Identity Document Theft in Polokwane Policing Area, South Africa - Moyahabo Rakololo, William; Maluleke, Witness; Barkhuizen, Jaco (International Journal of Criminology and Sociology, 2022)
This study explores the challenges of forensic technology in responding to Identity Document (ID) theft as an approach used by the South African Police Service (SAPS) in the Polokwane policing area. This study further evaluates the availability of technological and conventional resources to respond to this scourge, as well as the capabilities of the SAPS to utilise the available [lack of forensic technology] resources to respond best to ID theft. This was done by analysing preventative measures, associated with these challenges, as faced by SAPS and other relevant stakeholders on responding to this crime in the Polokwane Central Business District (CBD), Bendor Park, and Flora Park, coupled with the number of stores situated in the business sectors of these selected areas. For this study, the researchers adopted a quantitative research approach with 90 respondents in the identified areas. This study established that the secretive nature of ID theft makes it difficult for the relevant stakeholders (Not limited to the local SAPS, Businesses, and Public members as presented by this study) to effectively respond to this scourge. Negatively, the forefront gatekeepers to respond to this crime are mainly SAPS Constables with less training to investigates ID theft properly. Thus, find themselves being more reactive than proactive, which contributes to the difficulty of locating potential perpetrators in the process of conventional investigations applications. Furthermore, ID thieves utilise advanced technological resources (I.e. Computer hacking software), as opposed to SAPS which does not have systems nor capacity to effectively respond to this crime. The limited resources at the disposal of SAPS also renders its effort in responding to this crime inadequate. For recommendations; significant emphases should be directed on the promotion of public awareness through public education for the use of forensic technology as an investigative and identification tool of responding to ID theft. The intensive training of SAPS officials and inter-governmental corroboration between SAPS, Department of Home Affairs (DHA), and other relevant stakeholders in understanding this technology are highly advised.